2011
DOI: 10.1016/j.immuni.2011.03.027
|View full text |Cite
|
Sign up to set email alerts
|

DDX1, DDX21, and DHX36 Helicases Form a Complex with the Adaptor Molecule TRIF to Sense dsRNA in Dendritic Cells

Abstract: SUMMARY The innate immune system detects viral infection predominantly by sensing viral nucleic acids. We report the identification of a viral sensor, consisting of RNA helicases DDX1, DDX21, and DHX36, and the adaptor molecule TRIF, by isolation and sequencing of poly I:C-binding proteins in myeloid dendritic cells (mDCs). Knockdown of each helicase or TRIF by shRNA blocked the ability of mDCs to mount type I interferon (IFN) and cytokine responses to poly I:C, influenza A virus, and reovirus. Although DDX1 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
337
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(355 citation statements)
references
References 53 publications
(85 reference statements)
8
337
0
2
Order By: Relevance
“…They also showed that BTV activates the IFN-␣/␤ signaling pathway in pDCs via the MyD88 adaptor, as well as by the PKR and JNK kinases. Recently, a complex of cytoplasmic helicases including DDX1 has been identified as a new dsRNA sensor that uses the TRIF pathway to induce IFN-␣/␤ synthesis in the cytosol of DCs (67). Interestingly, this complex appeared essential for IFN-␤ production in response to reovirus infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also showed that BTV activates the IFN-␣/␤ signaling pathway in pDCs via the MyD88 adaptor, as well as by the PKR and JNK kinases. Recently, a complex of cytoplasmic helicases including DDX1 has been identified as a new dsRNA sensor that uses the TRIF pathway to induce IFN-␣/␤ synthesis in the cytosol of DCs (67). Interestingly, this complex appeared essential for IFN-␤ production in response to reovirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…5A). The expression of these gene products was silenced to target the two major canonical signaling pathways involved in viral sensing (i.e., the RLR and TLR pathways) and the recently described TRIF-dependent DexD/Hbox helicases (67). As shown in Fig.…”
Section: Btv Triggers Ifn-␤ Synthesis Through a Mavs-dependent Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance, TRIF but not MyD88 is upregulated in HTNV-infected cells [20]. The TRIF-connected DDX1-DDX21-DHX36 complex, a cytoplasmic viral sensor consisting of several RNA helicases, could also be involved in HTNV-induced HLA-I enhancement [43]. Similarly, RIG-I KD A549 cells and parental A549 cells treated with BX795, which blocks the TBK1/IKKε signaling axis [27], failed to increase HLA-I surface expression upon HTNV infection.…”
mentioning
confidence: 83%
“…Identifying such a novel complex would be highly relevant to the understanding of the molecular events involved in Poly(I:C)-triggered apoptosis as TRIF is also known to interact with the dsRNA sensor helicases complex DDX1-DDX21-DHX36 15 , and with the RIGI and MDA5 adapter VISA (also known as IPS-1) 16 to signal innate immune responses.…”
mentioning
confidence: 99%